2019
DOI: 10.11648/j.wcmc.20190701.12
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Optimal 3D placement of UAV with Minimum Transmit Power

Abstract: Due to vast technology advancement in communication System, it has been possible to use unmanned aerial vehicle (UAV) that can fly independently and worked remotely without carrying any human personnel. UAV provides new methods for communication in military and civilian application. They have small operating and installation cost. They provide flexible way for communication. Unmanned aerial vehicle can be used as Wireless base station in cellular system providing an alternative communication mechanism for cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A WSN is a network of dispersed sensors with low power, low storage capacity, and limited processing capabilities that sense and relay data to a SN [1][2][3][4][5]. In the concept of a 5G communication system, WSNs can be used to monitor the health system, agriculture, oil and gas exploration, smart homes and security, military applications, environmental monitoring, and industrial machine status [6][7][8]. In contrast, sensors constitute of finite battery life that bottleneck the efficiency of the network [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A WSN is a network of dispersed sensors with low power, low storage capacity, and limited processing capabilities that sense and relay data to a SN [1][2][3][4][5]. In the concept of a 5G communication system, WSNs can be used to monitor the health system, agriculture, oil and gas exploration, smart homes and security, military applications, environmental monitoring, and industrial machine status [6][7][8]. In contrast, sensors constitute of finite battery life that bottleneck the efficiency of the network [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the delay was less for low arrival rates and increased for high arrival rates [27] Optimal UAV placement to maximize the sum rate by using a minimum transmit power Genetic algorithm…”
Section: Centralized Algorithmmentioning
confidence: 99%
“…Zhang et al (2018) proposed a Dynamic droNe-bAse-station-Placement (D-NAPE) algorithm to solve the 3-D Dronemounted base-stations (DBS) placement problem by incorporating In-band full-duplex (IBFD)enabled DBSs communications for both access links and backhaul links of DBSs [14]. To achieve a better signal to noise ratio for an indoor UAV's optimal placement and minimum transmit power, Mahmood et al (2019) used Genetic algorithm and Nomad for their investigation [15]. To maximizes the number of covered users using the minimum transmit power, Alzenad et al (2019) proposed an algorithm for an optimal placement for UAV-BSs [16].…”
Section: Literature Reviewmentioning
confidence: 99%